Decrypting protein surfaces by combining evolution, geometry, and molecular docking. Issue 11 (26th June 2019) - Dequeker, Chloé; Laine, Elodie; Carbone, Alessandra
Abstract: The growing body of experimental and computational data describing how proteins interact with each other has emphasized the multiplicity of protein interactions and the complexity underlying protein surface usage and deformability. In this work, we propose new concepts and methods toward deciphering such complexity. We introduce the notion of interacting region to account for the multiple usage of a protein's surface residues by several partners and for the variability of protein interfaces coming from molecular flexibility. We predict interacting patches by crossing evolutionary, physicochemical and geometrical properties of the protein surface with information coming from complete cross‐docking (CC‐D) simulations. We show that our predictions match well interacting regions and that the different sources of information are complementary. We further propose an indicator of whether a protein has a few or many partners. Our prediction strategies are implemented in the dynJET 2 algorithm and assessed on a new dataset of 262 protein on which we performed CC‐D. The code and the data are available at:http://www.lcqb.upmc.fr/dynJET2/ .